2016
DOI: 10.1590/s1806-92902016001000002
|View full text |Cite
|
Sign up to set email alerts
|

Management of consecutive cuts in the production and quality of wintergreen paspalum seeds

Abstract: -The objective of this study was to evaluate the practice of consecutive cuts in the production and quality of Paspalum guenoarum seeds of the "Azulão" ecotype. The experimental design used was in completely randomized blocks with four replications. The treatment included three cuts in succession: zero cut, one cut, two cuts, and three cuts. The variables were: number of total tillers/plant; number of vegetative tillers/plant; number of reproductive tillers/plant; percentage of reproductive tillers; number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
(28 reference statements)
3
4
0
Order By: Relevance
“…[10] These findings clearly show that FTP and IN had a positive relationship (Table 5). This corroborates with previous results [43], which reported that late cuts in relation to the cycle of forage grasses can have negative effects on the productivity of seeds, possibly by reducing the photosynthetic area and eliminating reproductive parts of the tiller. The increased IN in the closing cut treatments was found to be related to the increased seed yields.…”
Section: Soil and Weather Conditionssupporting
confidence: 93%
See 1 more Smart Citation
“…[10] These findings clearly show that FTP and IN had a positive relationship (Table 5). This corroborates with previous results [43], which reported that late cuts in relation to the cycle of forage grasses can have negative effects on the productivity of seeds, possibly by reducing the photosynthetic area and eliminating reproductive parts of the tiller. The increased IN in the closing cut treatments was found to be related to the increased seed yields.…”
Section: Soil and Weather Conditionssupporting
confidence: 93%
“…'OKI-1' was 147-163 days (15 June-1 July) before seed harvest. The total number of tillers, the percentage of tillers that went through the reproductive stage, and the number of reproductive tillers are the variables that are most highly correlated with seed production [43]. Several studies (e.g., [44][45][46]) have reported that optimum tiller density affects increased forage and seed yields.…”
Section: Soil and Weather Conditionsmentioning
confidence: 99%
“…A similar lack of biomass response was observed in P. dilatatum (Bungenstab et al, 2013). Paspalum guenoarum improved its biomass when subjected to two cuttings rather than one cutting (Lopes et al, 2016). Vigorous regrowth of aerial structures does not always generate a similar gain in biomass due to the different energetic and structural prices of plant modules that need to be formed.…”
Section: Vegetative Parameters Biomass and Tissue Nitrogen Contentmentioning
confidence: 99%
“…Light-improving conditions stimulate basal buds to form new tillers (Baréa et al, 2007;Beck, 2012). In contrast, P. atratum (Hare et al, 2001) and P. dilatatum [biotype Virasoro;Scheffer-Basso et al (2007); ecotype Bagual; Beck (2012)] showed no cutting effect on tiller production, and Paspalum guenoarum ecotype Azulão decreased the number of tillers after two consecutive cuts (Lopes et al, 2016). The plant species may also differ in their capacity to regrow and produce new leaves.…”
Section: Vegetative Parameters Biomass and Tissue Nitrogen Contentmentioning
confidence: 99%
“…According to the literature, the main components of the production of Paspalum seeds are the TT, RT, NSI and WTS traits (Lopes and Franke 2011, Lopes et al 2016, Lopes et al 2017. The use of these traits favors the choice of superior performance genotypes, through indirect selection in traits of difficult selection and measurement, such as seed production.…”
Section: Rr Lopes Et Almentioning
confidence: 99%